Comparison of extraction techniques for three Calophyllum species and their antioxidant activity = Perbandingan teknik pengekstrakan untuk tiga spesies Calophyllum dan aktiviti antioksidan - Ramli, Siti Nurhafizah; Aminudin, Nurul Iman; Ahmad, Farediah; Darnis, Deny Susanti (The Malaysian Analytical Sciences Society, 2019)
Calophyllum is a pan-tropical genus belonging to the Guttiferae family and is known in Malaysia as ‘bintangor’. There has been continual interest to further investigate the phytochemistry of Calophyllum species since this genus is a rich source of active secondary metabolites, which show anti-HIV, cytotoxicity, and antimicrobial properties. This study was conducted to investigate the effect of extraction techniques on the phytochemicals content and antioxidant activity of the barks, leaves, and heartwood extracts of three Calophyllum species, namely C. incrassatum, C. rubiginosum, and C. canum. Soxhlet and maceration extraction techniques by using methanol as solvent were chosen in this study. The maceration extraction technique produced higher percentage yield as compared to Soxhlet extraction for leaves and barks of the three Calophyllum species. The highest percentage yield was obtained from the bark extract of C. canum (21.76%), followed by the bark extract of C. rubiginosum (20.24%) and leaves extract of C. rubiginosum (19.34%). Meanwhile, the Soxhlet extraction technique gave higher percentage yield as compared to the maceration technique for heartwood extracts of all samples. The phytochemical screening test revealed that all extracts contained tannin, phenol, flavonoid, terpenes, cardiac glycoside, coumarin, and phytosterol. The highest total phenolic content was obtained from Soxhlet extraction technique. The bark extract of C. canum displayed the highest phenolic content (461.90 mg GAE/g), followed by the bark extract of C. incrassatum (394.52 mg GAE/g) and leaves extract of C. incrassatum (227.89 mg GAE/g). The bark extract of C. canum showed the lowest IC50 value (3.07 μg/mL), followed by the bark extract of C. incrassatum (5.12 μg/mL) and leaves extract of C. incrassatum (5.93 μg/mL). Pearson’s correlation test showed a positive correlation between total phenolic content and DPPH radical scavenging activity.